If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4x + -20) = 0 Reorder the terms: (-20 + 4x) = 0 Remove parenthesis around (-20 + 4x) -20 + 4x = 0 Solving -20 + 4x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '20' to each side of the equation. -20 + 20 + 4x = 0 + 20 Combine like terms: -20 + 20 = 0 0 + 4x = 0 + 20 4x = 0 + 20 Combine like terms: 0 + 20 = 20 4x = 20 Divide each side by '4'. x = 5 Simplifying x = 5
| y-x=32 | | ((9x-11)+(7x-3))=((4x+1)(4x+1)) | | -9x-3x+4=-10x-(2x-4) | | 288=27x+18 | | 5(2h+3)-4h= | | 90=-5x-5(x-8) | | -8x+9=2x+49 | | 2x-5-4x=17 | | 11+20x=22x-1 | | 20/258 | | -x+4q=41 | | A=77-14.99n | | 9b+4=-23 | | 0=9-1/50x^2 | | -201=4n+7(1-8n) | | -3x-5(x-2)=4 | | 8r^4-r^2= | | 2h+(6h+h)+12= | | 4x+10h=5x+17 | | x^4+3x^3-3x^2-7x+6=0 | | -2+13x=50 | | 3x^3-15x^2-12x=0 | | x+6y=164 | | 3x-17=50 | | 3x+(x)+2=x+5 | | Log27(5x-1)=1/3 | | 23.24=4g+3.84 | | 3x+7=11+4x | | 2x-3(x+4)=21 | | -8v^2-8v+3=0 | | 5*5+10-0= | | 6x^2y+12xy= |